IMPROVEMENT OF SCIENCE PROCESS SKILLS THROUGH DISCOVERY LEARNING MODEL IN PHYSICS EDUCATION STUDENTS - Sugiarti Sugiarti; Dwi Ratnaningdyah (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2020)
Discovery Learning Model is a learning model that guides students to make discoveries through a series of inquiry and discovery activities. The purpose of this study is to describe the ability to improve students' science process skills in Basic Physics course material after the discovery learning model is applied. This research method is a quasi-experimental method because subjects are not randomly grouped, but are accepted as is. And the research design used was a one shot pretest-posttest design. The improvement of science process skills in the observation aspect is the science process skills that have the highest gain that is equal to 0.62 followed then by the science process skills in the measurement and concluding aspects of 0.61 and 0.58. While the lowest gain in science process skills is the science process skills in the classification and predicting aspects of 0.38 and 0.34. The average increase in science process skills in the Basic Physics course is 0.51 in the medium category.